Arabic Language Learning Design ARCS Model (Attention, Relevance, Confidence, and Satisfaction) John Keller's Perspective - Octaria, Fevi; Erlina, Erlina (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
The lack of student motivation in learning Arabic is something that needs to be found a solution. This is due to the need to create passionate and enjoyable learning. This research aims to 1). describe the nature of ARCS-based learning design in Arabic subjects, 2). Describe the syntax of the ARCS model in Arabic language learning. This research uses a qualitative approach to the type of library research with analytical descriptive methods. The findings of this research are 1) Arabic language learning design John Keller's ARCS model (Attention, Relevance, Confidence, and Satisfaction) is a motivation-based learning model based on a humanistic approach and behavioristic learning theory. The ARCS model is a model that does not stand alone but is implemented in integrated learning with other methods. 2) The learning syntax in the Attention model is how a teacher attempts to attract students' attention and maintain that attention and create curiosity. The learning syntax in the Relevance model is how a teacher attempts to adapt Arabic lesson material to students' daily lives. The learning syntax in the Confidence model is how a teacher attempts to create students' self-confidence in learning Arabic. Meanwhile, the learning syntax in the Saticfaction model is how the teacher attempts to provide rewards and reinforcement to create a sense of satisfaction for students in learning Arabic.